(untitled) (The Review of Diabetic Studies, 2025)
Background: The integration of wearable technologies into pediatric healthcare has transformed chronic illness management by enabling continuous, non-invasive monitoring. These devices offer real-time insights into physiological parameters, physical activity, and adherence, helping clinicians and families make data-driven decisions (Adepoju et al., 2025; Magsayo & Firoozabadi, 2025). Objective: This review systematically examines evidence from 14 empirical studies to evaluate the impact of wearable technologies and digital health interventions on disease monitoring, treatment adherence, and psychological outcomes in children with chronic illnesses. Methods: Following PRISMA 2020 guidelines, peer-reviewed articles published between 2014 and 2025 were reviewed. Eligible studies included randomized controlled trials, observational studies, and cross-sectional analyses involving children with chronic diseases monitored or treated using wearable or digital tools. Results: Wearables improved clinical management and behavioral outcomes across several chronic conditions, including asthma, cystic fibrosis, diabetes, obesity, autism, and ADHD. Devices facilitated early detection of physiological changes (van der Kamp et al., 2020), enhanced treatment engagement (Burckhardt et al., 2019), and promoted physical activity (Brudy et al., 2020; Black & Brunet, 2021). Psychosocial benefits such as reduced anxiety and improved motivation were observed through gamified and app-based interventions (Sanchez et al., 2017; Wantanakorn et al., 2018). Conclusion: Wearable technologies demonstrate strong potential for improving pediatric chronic illness management through personalized, data-driven approaches. Continued innovation, combined with behavioral and family-based support, can enhance adherence, psychological well-being, and health outcomes.